Walk 2 DECEMBRISTS - -, - (project baikal, 2011)
Polkanov’s House. The House Transferred from Dekabrskikh Sobyty Street 47 to Dekabrskikh Sobyty Street 77Tourist and Informational Center of Irkutsk City AdministrationThe House located on Dekabrskikh Sobyty Street 77bMini Park of the Symbols of Twin CitiesImprovement of Dekabrskikh Sobyty Street in Irkutsk(between Yamskaya Street and Timiryaseva Street). Graduation Project